ANALISIS FAKTOR-FAKTOR YANG DIPERTIMBANGKAN NETIZEN DALAM MELAKUKAN TRANSAKSI E-COMMERCE DI KOTA PONTIANAK - Hijrah Wahyudi (Jurnal Ekonomi Integra, 2017)
This research aim to know factors considered by netizen in Kotamadya Pontianak in doing transaction of e-commerce. This analysis can be finalized by using descriptive analysis and factor analysis. This research entangles the netizen a number of100 mans livinging in Kota Pontianak. Sample is taken at random. This research concludes that out of 14 variables simply there are 10 variables considered by netizen in doing transaction of e-commerce. Result of factor loadings indicates 10 divisible variable become two primary factor.